Additive effects of obesity and vitamin D insufficiency on all-cause and cause-specific mortality - Song, Shuaihua; Yuan, Yuan; Wu, Xiaolong; Zhang, Di; Qi, Qianjin; Wang, Haoran; Feng, Li (Frontiers in Nutrition, 2022)
Obesity and vitamin D deficiency are both considered risk factors for mortality, but the potential additive effects of vitamin D status and obesity on mortality has not been well studied. We aimed to examine the possible additive effects of obesity and vitamin D status on all-cause and cause-specific mortality. The data from the NHANES III (1988 - 1994) and NHANES 2001–2014 surveys were used, and multivariate Cox regression models were performed to assess the additive effects of vitamin D status and overweight/obesity/abdominal obesity on the all-cause, cardiovascular and cancer mortality, by stratifying Cox Hazard Ratios (HRs) across different categories of vitamin D status and body mass index (BMI) and waist circumference (WC) categories. The models were adjusted for age, race/ethnicity, gender, educational level, family income to poverty ratio, leisure-time physical activity, smoking and drinking. Across all BMI/WC categories, there was an additive effect of the vitamin D both insufficiency and deficiency on all mortality rates, with deficiency having much stronger effect than insufficiency. Interestingly, the effect of vitamin D deficiency overcame the effect of obesity on all mortality rates. The highest HRs for overall and cardiovascular mortality were observed among vitamin D deficient obese/abdominally obese subjects, while for cancer mortality among vitamin D deficient normal weight/non-abdominally obese subjects. In stratified analyses, regarding all-cause mortality, there was an additive effect of the vitamin D both insufficiency and deficiency in all BMI/WC categories. Regarding cardiovascular mortality, there was an additive effect of vitamin D deficiency in all BMI/WC categories, but the additive effect of vitamin D insufficiency reached significance only in normal weight subjects. Regarding cancer mortality, the effect did not reach significance among obese subjects for vitamin D deficiency, while for insufficiency, significance was reached only among non-abdominally obese subjects. Interestingly, vitamin D surplus was associated with increased risk for cancer mortality in obese subjects, but there was an inadequate number of subjects in this category to make proper judgment. In conclusion, vitamin D insufficiency and deficiency gradually increase risk for mortality across all BMI/WC categories. In our analyses, vitamin D deficiency overcame the effect of obesity on mortality rates.